(99m)Tc-Galacto-RGD(2): A Novel (99m)Tc-Labeled Cyclic RGD Peptide Dimer Useful for Tumor Imaging - Ji, Shundong (2013)
This study sought to evaluate [(99m)Tc(HYNIC-Galacto-RGD(2))(tricine)(TPPTS)] ((99m)Tc-Galacto-RGD(2): HYNIC = 6-hydrazinonicotinyl; Galacto-RGD(2) = Glu[cyclo[Arg-Gly-Asp-D-Phe-Lys(SAA-PEG(2)-(1,2,3-triazole)-1-yl-4-methylamide)]](2) (SAA = 7-amino-L-glycero-L-galacto-2,6-anhydro-7-deoxy-heptanamide, and PEG(2) = 3,6-dioxaoctanoic acid); and TPPTS = trisodium triphenylphosphine-3,3',3"-trisulfonate) as a new radiotracer for tumor imaging. Galacto-RGD(2) was prepared via the copper (I)-catalyzed 1,3-dipolar azide–alkyne Huisgen cycloaddition. HYNIC-Galacto-RGD(2) was prepared by reacting Galacto-RGD(2) with sodium succinimidyl 6-(2-(2-sulfonatobenzaldehyde)hydrazono)nicotinate (HYNIC-OSu) in the presence of diisopropylethylamine, and was evaluated for its integrin α(v)β(3) binding affinity against (125)I-echistatin bound to U87MG glioma cells. The IC(50) value for HYNIC-Galacto-RGD(2) was determined to be 20 ± 2 nM. (99m)Tc-Galacto-RGD(2) was prepared in high specific activity (~185 GBq/µmol) and high radiochemical purity (>95%), and was evaluated in athymic nude mice bearing U87MG glioma xenografts for its tumor-targeting capability and biodistribution. The tumor uptake of (99m)Tc-Galacto-RGD(2) was 10.30 ± 1.67, 8.37 ± 2.13, 6.86 ± 1.33 and 5.61 ± 1.52 %ID/g at 5, 30, 60 and 120 min p.i., respectively, which was in agreement with high integrin α(v)β(3) expression on glioma cells and neovasculature. Its lower uptake in intestines, lungs and spleen suggests that (99m)Tc-Galacto-RGD(2) has advantages over (99m)Tc-3P–RGD(2) ([(99m)Tc(HYNIC-3P–RGD(2))(tricine)(TPPTS)]: 3P–RGD(2) = PEG(4)-E[PEG(4)-c(RGDfK)](2); PEG(4) = 15-amino-4,7,10,13-tetraoxapentadecanoic acid) for imaging tumors in the chest and abdominal regions. U87MG tumors were readily detected by SPECT and the tumor uptake of (99m)Tc-Galacto-RGD(2) was integrin α(v)β(3)-specific. (99m)Tc-Galacto-RGD(2) also had very high metabolic stability. On the basis of results from this study, it was concluded that (99m)Tc-Galacto-RGD(2) is an excellent radiotracer for imaging integrin α(v)β(3)-positive tumors and related metastases.